Study of the Dependence of Reaction Sensitivity on the Chemistry of Complex Formation - Atoev Ekhtiyor Khudoyorovich; Bekov Ulugbek Safarovich (Peerian Journals Publishing, 2022)
this article is devoted to the problems of studying the sensitivity of the reaction from the chemistry of complex formation, the influence of the pH of the medium on the yield of the reaction product. An equation is given for the dependence of the sensitivity of reactions on chemistry, and primary conclusions are made regarding the relationship between sensitivity and chemistry of complex formation
Keywords: complex formation; reaction sensitivity; reaction chemistry; selectivity